2016
DOI: 10.1038/nrendo.2016.175
|View full text |Cite
|
Sign up to set email alerts
|

The endocrine manifestations of anorexia nervosa: mechanisms and management

Abstract: Anorexia nervosa is a psychiatric disorder characterized by altered body image, persistent food restriction and low body weight, and is associated with global endocrine dysregulation in both adolescent girls and women. Dysfunction of the hypothalamic-pituitary axis includes hypogonadotrophic hypogonadism with relative oestrogen and androgen deficiency, growth hormone resistance, hypercortisolaemia, non-thyroidal illness syndrome, hyponatraemia, and hypooxytocinaemia. Serum levels of leptin, an anorexigenic adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
146
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(160 citation statements)
references
References 192 publications
(234 reference statements)
4
146
0
10
Order By: Relevance
“…Additionally, stress increases epinephrine, cortisol, growth hormone (GH), and glucagon, and has been observed in combination with low triiodothyronine (T 3 ) concentrations in AN (Schorr & Miller, 2017). Furthermore, GH is elevated in AN (Schorr & Miller, 2017) and may have a direct lipolytic effect independent from insulin-like growth factor 1 (IGF-1), increasing especially LDL concentrations (Misra et al, 2006). It shows significantly higher activity in AN compared with HC (Ohwada et al, 2006).…”
Section: Random Effects Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, stress increases epinephrine, cortisol, growth hormone (GH), and glucagon, and has been observed in combination with low triiodothyronine (T 3 ) concentrations in AN (Schorr & Miller, 2017). Furthermore, GH is elevated in AN (Schorr & Miller, 2017) and may have a direct lipolytic effect independent from insulin-like growth factor 1 (IGF-1), increasing especially LDL concentrations (Misra et al, 2006). It shows significantly higher activity in AN compared with HC (Ohwada et al, 2006).…”
Section: Random Effects Modelmentioning
confidence: 99%
“…Adipose tissue plays an important role in the regulation of insulin sensitivity, and cross-talk between glucose and lipid metabolism occurs (Saltiel & Kahn, 2001). Additionally, stress increases epinephrine, cortisol, growth hormone (GH), and glucagon, and has been observed in combination with low triiodothyronine (T 3 ) concentrations in AN (Schorr & Miller, 2017 (Ohwada et al, 2006). However, high T 3 (Rigaud et al, 2009;Weinbrenner et al, 2004;Zák et al, 2005) and low T 3 (Matzkin et al, 2006) have been associated with increased HDL, but one study showed no association (Ohwada et al, 2006), rendering results inconclusive.…”
Section: Random Effects Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most questioning features of individuals with AN is their ability to chronically restrict energy intake, whereas they are in an emaciated condition often for many years, and not rarely to the point of death. These alterations of interoception clearly illustrate a communication breakdown between the body and the brain, that is, the inability of the brain to translate circulating factors that signal the energy state of the organism into the appropriate adaptive behavior [4]. In fact, recent genome-wide association studies provide evidence of a genetic predisposition for a lower body weight set-point in AN and also indicate that it is not merely a psychiatric but also a metabolic disorder [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…This is in stark contrast with the common misperception that eating disorders are trivial and self-imposed problems 8. The physical complications of eating disorders are partially to malnutrition, including acute metabolic or electrolyte disturbances, gastrointestinal or cardiac complications,9 10 fertility and perinatal complications,11 bone metabolic12 or endocrine13 problems, growth and developmental delay in children. In addition, certain physical illnesses are associated with eating disorders.…”
Section: Introductionmentioning
confidence: 96%